PREFERENSI KONSUMEN TERHADAP PRODUK KERUPUK IKAN HARUAN DI KOTA BANJARMASIN - Nur Hidayat Eko Prasetyo; Leila Ariyani; Idiannor Mahyudin (Universitas Lambung Mangkurat, 2022)
One of the ways to develop this Snakehead Fish cracker product is by knowing consumer preferences for Snakehead Fish crackers, and helping producers to determine whether the products they make have met the expectations of consumers. This study aims to analyze consumer preferences for Snakehead Fish crackers in the city of Banjarmasin. This research method is qualitative using organoleptic test for sensory factors, interviews and questionnaires for psychological factors and marketing factors. Producer location is done by purposive sampling method. Where it is known the location or place of production of Snakehead Fish crackers, namely 10 groups in Banjarmasin City. Based on the results obtained, it can be concluded that of the three preference factors, namely sensory, psychological and marketing, the assessment of all respondents is above 70. Sensory factors are between 72 – 86, psychological factors are 89 – 97 and marketing factors are 71 – 79. Preference results are in the form of Most of the suggestions written are in the marketing factor, which is 57%, for suggestions on the sensory factors 34% and others including those who have received or not given 9% advice and consumer advice.